The influence of an Antarctic glacier tongue on near‐field ocean circulation and mixing. Issue 4 (14th April 2014) - Stevens, C. L.; McPhee, M. G.; Forrest, A. L.; Leonard, G. H.; Stanton, T.; Haskell, T. G.
Abstract In situ measurements of flow and stratification in the vicinity of the Erebus Glacier Tongue, a 12 km long floating Antarctic glacier, show the significant influence of the glacier. Three ADCPs (75, 300, and 600 kHz) were deployed close (<50 m) to the sidewall of the glacier in order to capture near‐field flow distortion. Scalar (temperature and conductivity) and shear microstructure profiling captured small‐scale vertical variability. Flow magnitudes exceeded 0.3 m s−1 through a combination of tidal flow (∼8 cm s−1) and a background/residual flow (∼4–10 cm s−1) flowing to the NW. Turbulence was dominated by deeper mixing during spring tide, likely indicative of the role of bathymetric variation which locally forms an obstacle as great as the glacier. During the neap tide, near‐surface mixing was as energetic as that seen in the spring tide, suggesting the presence of buoyancy‐driven near‐surface flows. Estimates of integrated dissipation rate suggest that these floating extensions of the Antarctic ice sheet alter energy budgets through enhanced dissipation, and thus influence coastal near‐surface circulation.